EFFECT OF BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) AND DEBT TO EQUITY RATIO (DER) TOWARD RETURN ON ASSETS (ROA) (CASE STUDY BANKING COMPANY BASED ON CAPITAL PERSPECTIVE LISTED ON THE INDONESIAN STOCK EXCHANGE (IDX) FOR PERIOD 2017-2019) - Fika Aryani (Neraca : Jurnal Akuntansi Terapan, 2022)
This study aims to detect the effect Beban Operasional Pendapatan Operasional (BOPO) to Return On Assets (ROA); effect of Debt to Equity Ratio (DER) to Return On Assets (ROA); effect of BOPO and DER test simultaneously to Return On Assets (ROA) Banking Company Based on Capital Prespective on The Indonesia Stock Exchange (IDX) for Period 2017-2019.  This study was conducted based on Associative Reasearch. Multiple Regression was used as analysis technique, with sample amount of 7 Bank using by saturation Sampling Technique. The results showed that the analysis of BOPO ratio has negatif effects and significant to ROA; DER has negative effect and not significant to ROA. While simultaneously, BOPO and DER do significantly influence to Retun On Assets (ROA).